2019
DOI: 10.1016/j.neuroimage.2019.03.031
|View full text |Cite
|
Sign up to set email alerts
|

The spatiotemporal neural dynamics underlying perceived similarity for real-world objects

Abstract: The degree to which we perceive real-world objects as similar or dissimilar structures our perception and guides categorization behavior. Here, we investigated the neural representations enabling perceived similarity using behavioral judgments, fMRI and MEG. As different object dimensions co-occur and partly correlate, to understand the relationship between perceived similarity and brain activity it is necessary to assess the unique role of multiple object dimensions. We thus behaviorally assessed perceived ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
66
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 101 publications
7
66
2
2
Order By: Relevance
“…One important difference between our experiment and previous studies that have used inverse MDS is that rather than selecting items that fall into clear categorical groups such as faces, bodies or animals 26,28,30 , the items in our set were highly heterogeneous. Our stimuli and design therefore permit a unique exploration of the characteristics that observers use to define and differentiate between objects in the absence of cues that would otherwise bias sorting criteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One important difference between our experiment and previous studies that have used inverse MDS is that rather than selecting items that fall into clear categorical groups such as faces, bodies or animals 26,28,30 , the items in our set were highly heterogeneous. Our stimuli and design therefore permit a unique exploration of the characteristics that observers use to define and differentiate between objects in the absence of cues that would otherwise bias sorting criteria.…”
Section: Resultsmentioning
confidence: 99%
“…As in previous studies of image vision (e.g. [25][26][27][28]35 ), the 2-D images were scaled so that they had the same visual size.…”
Section: Resultsmentioning
confidence: 99%
“…What are the representational dimensions in other domains, such as words, faces, places, or actions? Finally, what makes those representations similar to those found in deep convolutional neural network models of vision 47 , semantic embeddings learned on word co-occurrence statistics in large text corpora 22,30,48 , or brain activity in humans [49][50][51][52][53] ? Addressing these questions will be important for a comprehensive understanding of mental representations of objects across people and different domains.…”
Section: Discussionmentioning
confidence: 98%
“…Or do they partly reflect idiosyncratic preferences, that is an individual person's unique aesthetic preference for particular faces? To resolve this question, we performed an analysis where we modelled neural RDMs as a function of individual yes/no responses and attractiveness ratings, while controlling for the database ratings using partial correlation analysis [43][44][45] (Figure 2c). We found that individual attractiveness judgments still significantly predicted cortical representations, both when considering yes/no responses (from the 150-200ms time bin; peaking at 600-650ms, peak t [22]=3.87, p<0.001, pcorr=0.002) and when considering attractiveness ratings (from the 150-200ms time bin; peaking at 500-550ms, peak t [22]=3.90, p<0.001, pcorr=0.012).…”
Section: Early Representations Of Facial Attractiveness Reflect Indivmentioning
confidence: 99%
“…To establish correspondences between the neural RDM and a specific predictor RDM while controlling for other RDMs (see below), we used partial correlations [43][44][45]. All correlations were Fisher-transformed before entering them into statistical analyses.…”
Section: Tracking Neural Representations Of Facial Attractivenessmentioning
confidence: 99%